Journalism – a High-Risk Profession? The Impact of Politics on the Employment Security of Journalists in Poland in 2015–2023 - Mateja, Magdalena (Žurnalistikos tyrimai, 2024)
Raising questions about how risky it was (and still is) to practice journalism in Poland, author Magdalena Mateja examines cases from 2015 to 2023, when the Polish government not only regulated the public broadcaster TVP, but also interfered in the management of national commercial television and radio stations. During this period, journalists who did not please the authorities were fired from various media outlets. Among other things, the author concludes that in 2023, after the change of government, the situation of journalists did not improve either in the public broadcaster or in the media market as a whole.
Keywords: hiring; firing; government influence and pressure